AYBEK'S CONTRIBUTION TO THE DEVELOPMENT OF UZBEK LITERATURE OF THE XX CENTURY (Conference Zone, 2022)
The article scientifically analyzes the role of the heritage of the great poet of Uzbek literature of the twentieth century, statesman and translator Musa Tashmuhammad oglu Aybek in the development of society and the importance of his heritage in the education of young people.